Inseticidas agrícolas associados a atrativos alimentares no controle de Ceratitis capitata (Wiedemann, 1824) (Diptera: Tephritidae) - Batista, Aíla Rosa Ferreira (2023)
Fruit growing is one of the most important activities for Brazilian agribusiness, fostering employment and local income and expansion of productive niches, allowing economic advancement through the export of tropical and subtropical fruits, processed or in natura, for several countries. Brazil acts as the third largest producer worldwide, with about 350 botanical species distributed in approximately 65 families, which are affected by the attack of Ceratitis capitata (Wiedemann, 1824) (Diptera: Tephritidae). Due to the proliferation of this insect pest, the main control method used is the chemical control, carried out by full coverage or in the formulation of toxic baits with insecticides of the chemical groups of organophosphates, pyrethroids and spinosines. Thus, this study aimed to evaluate the mortality of C. capitata when exposed to fruits treated with toxic baits. The study was conducted at the Invertebrate Laboratory of the Center of Agricultural Sciences of the Federal University of Paraíba, under controlled conditions of temperature (25 ºC), relative humidity (70% 10%) and 12-hour photophase. Insecticides, malathion, deltamethrin and spinetoram were used alone and in association with Ceratrap®, Biofruit® and molasses. The treatments were diluted in minimum, recommended and maximum doses. After dilution, the solutions were applied on the fruits, which were stored in arenas, in a completely randomized design, with eight replicates per treatment, with mortality counted as a function of time. The data that did not show homogeneity were submitted to non-parametric statistics, the non-parametric Kruskal-Wallis test followed by the Dunn test, with significance of p≤0.05 of probability. The use of deltamethrin and spinetoram at the recommended dose presents higher mortality of C. capitata. The association of attractants in the minimum dose of deltrametrin and spinetoram caused the highest mortality of C. capitata. Ceratrap®, associated with spinetoram at the recommended dose and malathion at the maximum dose is efficient in controlling C. capitata. Biofruit® associated with malathion at the maximum dose causes mortality of C. capitata. Deltamethrin and malathion in the recommended dose associated with molasses reduces the number of pupae.